University Extension Program as an Educational Practice for Health Promotion - Regis Rodrigues Santana; Cristina Célia de Almeida Pereira Santana; Sebastião Benício da Costa Neto; Ênio Chaves de Oliveira (Universidade Federal do Rio Grande do Sul, 2021)
The aim of the article was to investigate the contributions of University Extension Programs in vocational training and health promotion. This was a review study, consulting the LILACS, MEDLINE and Scielo databases in June 2019. According to eligibility criteria, 18 articles were selected. After synthesis, the data were arranged in tables and charts. The descriptive-qualitative approach was the most used methodological approach with focus on multidisciplinary work, academic education and community-academy interaction. University extension was understood as a strategy to promote health and a feasible tool for professional development. However, it was considered necessary a greater incentive for its strengthening and social fulfillment.